LAMA WAKTU PROSES CURRING TERHADAP PRODUK RAMBAK KULIT IKAN TENGGIRI (Scomberomorus commersonii) - Purnomo Purnomo; Juhana Suhanda (Fish Scientiae, 2019)
Skin of narrow - barred Spanish mackerel has not been maximally utilized. It is alternatively used as chips. It has good taste obtained from immersion the fish skin into herbs and spices. The objective of the study was to find the optimum time length of immersing the mackerel’s skin into the spices. This study is expected to be able toproduce the desired chip product, diversify the processed fish products, create newhousehold industry, and provide scientific information on environmental friendly wasteutilization. The ingredients needed in chip processing of the mackerel chips were garlic,tamarind, lime, coriander, salt, and ginger. While research method used is RAL with one factor of different time (4 treatment and 3 replication) and analysis of water content, testprotein and organoleptic level.Results showed that the lowest water content occurred in treatment A, 11.10 %,and the highest in treatment C, 13.26 %, while the lowest protein was found in treatmentA, 24.50 %, and the highest in treatment D, 61.25%. Water content was statisticallysignificantly different and protein content was highly significantly different amongtreatments. The organoleptic test found that the lowest mean value occurred in treatmentA, 5.046, and the highest in treatment B, 5.294. The sensory test gave significant effectonly on the taste. This difference indicates that the immersion time length of thetreatments could also impact on water content or protein content.